ANALISIS SKALA USAHATANI PADI SAWAH SISTEM TANAM JAJAR LEGOWO DI KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA (GANEC SWARA, 2023)
The purpose of this study was to analyze the scale of lowland rice farming with the jajar legowo planting system in Lombok Baat Regency, with a total of 60 respondents determined by non-proportional random sampling and data analysis using Cobb-Douglas function analysis, followed by the F test and T.The results showed that: 1). Lowland rice farming with the jajar legowo system is at an increasing production scale (increasing Return To Scala). This is seen from the elasticity of production that is greater than one, namely (bi = 4.428) > 1, which means that if the use of inputs is increased, the proportion of additional production will be greater than the proportion of additional inputs, 2). It is integrated that production factors (land area, seeds, fertilizers, pesticides and labor) affect the level of production. This can be seen from the results of model testing using the Cobb-Douglas production function, F hit (33.921) > F tab (Z 1.645 = 0.95). and the value of the coefficient of determination (R2) is 0.861, which means that the magnitude of the influence of the independent variable on the dependent variable is 86.1%, while the remaining 13.9% is influenced by other factors outside the model, 3). the most dominant influence on the level of production (t hit (2,919) > t table (1,645),